Cerebral Small Vessel Disease Burden Is Associated With Poststroke Depressive Symptoms: A 15-Month Prospective Study - Liang, Yan; Chen, Yang-Kun; Mok, Vincent Chung-Tong; Wang, De-Feng; Ungvari, Gabor S.; Chu, Winnie Chiu-Wing; Kang, Hee-Ju; Tang, Wai-Kwong (Frontiers in Aging Neuroscience, 2018)
Objective: All types of cerebral small vessel disease (SVD) markers including lacunae, white matter hyperintensities, cerebral microbleeds and perivascular spaces were found to be associated with poststroke depressive symptoms (DS). This study explored whether the combination of the four markers constituting an overall SVD burden was associated with DS after stroke. Methods: A selected cohort of 563 patients with acute ischemic stroke were followed over 15-month period after index stroke. A score of ≥ 7 on the 15-item Geriatric Depression Scale (GDS) was defined as clinically significant DS. Scores of the four SVD markers ascertained on magnetic resonance imaging were summed up to represent the total SVD burden. The association between SVD burden and poststroke DS was assessed with generalized estimating equations models. Results: The study sample had a mean age of 67.0 years and mild-moderate stroke (National Institutes of Health Stroke Scale score: 3, interquartile, 1-5). DS were found in 18.3%, 11.6% and 12.3% of the sample at 3-, 9- and 15 months after stroke, respectively. After adjusting for demographic characteristics, stroke severity, physical and cognitive functions, and size and locations of stroke, the SVD burden was associated with an increased risk of DS (odds ratio=1.30; 95% confidence interval=1.07-1.58; p=0.010). Other significant predictors of poststroke DS were time of assessment, female sex, smoking, number of acute infarcts, functional independence and social support. Conclusions: SVD burden was associated with poststroke DS examined over 15 months follow-up in mild to moderate acute ischemic stroke.